Treatments for resectable esophageal cancer: from traditional systemic therapy to immunotherapy. Issue 18 (20th September 2022) - Yan, Yan; Feng, Xijia; Li, Chengqiang; Lerut, Toni; Li, Hecheng
Abstract : Abstract: Esophageal cancer (EC) has a high incidence and poor prognosis. The two major histological types, squamous cell carcinoma and adenocarcinoma, differ in their epidemiology and treatment options. Patients with locally advanced EC benefit from multimodal therapy concepts including neoadjuvant chemotherapy, neoadjuvant chemoradiotherapy, and perioperative chemotherapy. Currently, immunotherapy for the solid tumor is a hot spot. Treatment with adjuvant immune checkpoint inhibitors (ICIs) is the first immunotherapy for resectable EC listed in the latest National Comprehensive Cancer Network Guidelines for the Esophageal and Esophagogastric Junction Cancers. Recent clinical trials have established ICIs for three treatment models of resectable EC. Their short-term results demonstrated ideal efficacy and tolerable toxicity, though some concerns remain. This review summarizes the novel data on the ICIs for resectable EC and lists the registered related clinical trials. Hopefully, this review can provide a reference for ongoing research on the treatment options for resectable EC.